Implementasi Manajemen Strategi Dalam Meningkatkan Mutu Pendidikan Di Sekolah SMP Swasta Adhyaksa Darmakarini - Zulqaidah; Ella Nurmaini; Hasriyati Harahap; Ahmad Mukhlasin (CV Edujavare Publishing, 2023)
This research aims to describe or explain the implementation of strategic management in improving the quality of education. This research uses a qualitative research approach. Qualitative research is basically analysis-based research. The theoretical basis becomes a guide to ensure the research focus is in accordance with the facts in the field. Data collection in research is carried out using various research methods such as observation, interviews, literature and documentation, all that is needed are tools. For this reason, for quality education, strategies are needed to improve it, such as efforts to attend upgrading courses, take educational courses, increase reading opportunities, make visits to other schools, and establish relationships with student parents. This is one form of creating quality education. In running an educational institution, we need to know in advance what factors must be considered, namely the vision and mission must be clear and in line with educational goals to help develop the right strategy.